2012
DOI: 10.1101/sqb.2013.77.014779
|View full text |Cite
|
Sign up to set email alerts
|

Deep Sequencing from hen1 Mutants to Identify Small RNA 3' Modifications

Abstract: microRNAs (miRNAs) function via targeting of messenger RNAs, suppressing protein levels, and playing important roles in biological processes of plants and animals. The pathway for miRNA biogenesis is well established, but less is known about miRNA turnover, largely because of difficulties in capturing miRNAs during the process of decay, in which they are both rare and ephemeral. The HEN1 protein methylates the 3 0 terminus of small RNAs (sRNAs), protecting them from poly-urydilation and degradation. Recent pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 44 publications
(45 reference statements)
0
7
0
Order By: Relevance
“…This size shift could be due to sRNA truncation, polyuridylation, or a combination of both. To analyze the sRNA derivatives, we devised an informatics pipeline as follows (Zhai and Meyers, 2013): First, each non-genomematched sRNA read was divided into two parts, viz. the longest 59 genome-matched component head portion and a 39 tail portion (for the reads that perfectly mapped to the genome we assumed there was no tail); next, focusing first on miRNAs, we aligned the head portion of the reads to each miRBase-annotated miRNA (allowing only perfect matches) to determine the extent of tailing (addition of nontemplated 39 nucleotides) and truncation (shortening of the miRNA from the 39 end, usually prior to tailing).…”
Section: Sequencing Of Srnas From Plant Hen1 Mutantsmentioning
confidence: 99%
See 1 more Smart Citation
“…This size shift could be due to sRNA truncation, polyuridylation, or a combination of both. To analyze the sRNA derivatives, we devised an informatics pipeline as follows (Zhai and Meyers, 2013): First, each non-genomematched sRNA read was divided into two parts, viz. the longest 59 genome-matched component head portion and a 39 tail portion (for the reads that perfectly mapped to the genome we assumed there was no tail); next, focusing first on miRNAs, we aligned the head portion of the reads to each miRBase-annotated miRNA (allowing only perfect matches) to determine the extent of tailing (addition of nontemplated 39 nucleotides) and truncation (shortening of the miRNA from the 39 end, usually prior to tailing).…”
Section: Sequencing Of Srnas From Plant Hen1 Mutantsmentioning
confidence: 99%
“…For sRNA reads that were not genome matched, one nucleotide was chopped off from the 39 end in successive rounds until the remaining 59 sequence was perfectly mapped to the Arabidopsis genome as previously described (Zhai and Meyers, 2013). Thus, any non-genome-matched sRNA read could be split into two parts: a 59 head and a 39 tail.…”
Section: Bioinformatics Analysis Of Srnasmentioning
confidence: 99%
“…We next examined how broadly the monouridylated form of miR1510 exists in different tissues of soybean. We employed a previously described method for analysis of truncation and tailing of miRNAs (21). We analyzed the published data that comprise an atlas of soybean small RNAs (19) and observed that, as in the leaf tissue, miR1510 is uridylated to 22 nt in other tissues, including nodule, flower, and anther, although the degree of uridylation varies (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…We next examined how broadly the monouridylated form of miR1510 exists in different 75 tissues of soybean. We employed a previously described method for analysis of truncation and 76 tailing of miRNAs (31). We analyzed the published data that comprises an atlas of soybean small 77 RNAs (29); we observed that as with the leaf tissue miR1510 is uridylated to 22 nt in other tissues, 78…”
Section: Results 57mentioning
confidence: 99%